Presentation of three cases followed up with a diagnosis of Felty syndrome - Yazıcı, Ayten (Eur J Rheumatol, 2014)
An effective treatment strategy for Felty syndrome (FS) has not been developed so far. In this article, three cases with FS, who responded to different treatment modalities, have been presented. Case 1 was a 52-year-old male patient who initially received methotrexate, and then, he was switched to granulocyte colony-stimulating factor (G-CSF) and cyclosporine treatment when his neutropenia was further deteriorated. The patient needed monthly doses of G-CSF for nearly 6 months, and his steroid dose was increased. Afterwards, his neutropenia improved with cyclosporine, methotrexate, and hydroxychloroquine combination treatment. Case 2 was a 78-year-old female patient who was started on leflunomide, hydroxychloroquine, and 60 mg methylprednisolone. Case 3 was a 69-year-old female patient who was first treated with 32 mg methylprednisolone, G-CSF, and then with cyclosporine. Neutropenia of both patients improved, and their health status normalized at 2 months. Different treatment strategies have been tried for the management of FS; disease-modifying anti-rheumatic drugs have been used successfully alone or in combination with G-CSF. As seen in the last case, it should be kept in mind that patients can present predominantly with symptoms of infection or hematologic disorders.